Acceptability and feasibility of the World Health Organization's Caregiver Skills Training Programme (WHO CST) delivered via eLearning, videoconferencing, and in-person hybrid modalities in Hong Kong - Lau, Janet Siu-Ping; Lai, Simon Man-Kin; Ip, Florence To-Sau; Wong, Paul Wai-Ching; Team, WHO CST; Servili, Chiara; Salomone, Erica; Pacione, Laura; Shire, Stephanie; Brown, Felicity L. (Frontiers in Psychiatry, 2022)
Background. Local children with developmental disabilities were deprived of learning opportunities due to recent social and health incidents, resulting in elevating challenging behaviours and familial conflicts. This study explored the acceptability and feasibility of the World Health Organization’s Caregiver Skills Training Programme (WHO‐CST) in alternative delivery modes under new normal and post COVID-19 period. Method. The WHO‐CST were delivered via E-Learning (EL), Video-conferencing (VC), and In-Person Hybrid (IP) modes to 34 parent-child dyads, being randomly assigned to modes of asynchronous non-interfering EL (n=9), synchronous with online coaching VC (n=7), synchronous with in-person coaching IP (n=9), and Wait-list Control WLC (n=9). Data from two standardised scales of General Health Questionnaire (GHQ-12) and Strengths and Difficulties Questionnaire (SDQ), and post session and home visit feedback forms that included both structured and open-ended questions were collected before and after intervention. Both quantitative and qualitative approaches were used in studying the collected data. Results. High levels of acceptability and feasibility of the training programme were supported by ratings on comprehensiveness and relevance, agreement with their personal values, duration, and usefulness. IP and VC groups yielded more positive changes than EL and WLC groups with 3%, 16%, 13%, and -3% in General Health Questionnaire (GHQ-12), -13%, -15%, -6% and 0% in Difficulties-total, and 36.5%, 35.5%, 5.8% and 2.4% in Prosocial Scale at Strengths and Difficulties Questionnaire (SDQ) for EL, VC, IP, and WLC groups respectively from baseline to 12 weeks after intervention. Results from two standardised scales echoed with qualitative observations that the programme helped improve caregivers’ well-being, child’s communication, and behaviours across intervention groups. Conclusions. Current findings revealed that the WHO-CST delivered in three alternative modes were acceptable and feasible, and yielded positive impacts towards both caregivers and children. In-person coaching and skill-practicing sessions were effective in mitigating child’s challenging behaviours while personal interaction, either face-to-face or virtual, is a significant factor in uplifting caregivers’ well-being, whereas the self-learning model is popular among the busy caregivers. In clinical practice, needs and goals of families and the constraints of remote interventions at the settings should be balanced.